Pengaruh Penambahan Kulit Ari Kelapa Pada Pakan Untuk Pertumbuhan Dan Kelangsungan Hidup Ikan Mas (Cyprinus Carpio) - Yeni Puji Lestari Lestari; Nanda Diniarti; Dewi Putri Lestari (Journal of Fish Nutrition, 2022)
Goldfish (Cyprinus carpio) is one of the freshwater fish commodities that are very popular with the public both for consumption and as ornamental fish. This study aims to analyze the growth of carp fed with the use of coconut husks and the optimum dose to produce high growth and survival rates for carp. This research was conducted by experimental method using a completely randomized design (CRD) with 3 treatments and 5 replications. The treatments given were: Treatment 0: 100% feed formulation, Treatment 1: 90% feed formulation + 10% Coconut Arid Skin and Treatment C: 80% feed formulation + 20% Coconut Arid Skin. Based on the results of the research that has been carried out, it can be concluded that the P0 (Control) treatment gave an absolute weight growth of 26.11 grams, a specific growth of 13.26%, the best FCR P1 was 4.30 grams and the results of P1 feed efficiency were higher than other treatments that is equal to 24.26%. The survival of carp with the addition of coconut husk at a dose of 10% at 80% and a dose of 20% resulted in an SR of 72%, while the survival in the P0 treatment (control) without the use of coconut husk was 92%.